Integrated system for the surveillance and management of harmful algal blooms in coastal areas of the province of Cienfuegos, Cuba - Rojas-Abrahantes, Gabriel Liván (2023)
Harmful algal blooms can have negative consequences on the health, economy, and biological diversity of marine ecosystems. In the province of Cienfuegos, located in south-central Cuba, different bloom events have occurred in the bay of the same name, with a negative impact on the health and economy of the locality, as well as of the country. The objective of this research project was to design and implement a surveillance and management system of these events in the province of Cienfuegos, with the purpose of having well-defined intersectoral action mechanisms for the occurrence of these microorganisms, based on the principles of Integrated Management of Coastal Zones. During 2021, bloom events of these algae were scientifically confirmed; consequently, a workshop was developed for the design and proposal of this system, using the criteria of key specialists in the management of these events in the territory. The main characteristic of the monitoring and management system was to guarantee the integration of the sectors in the province related to this problem. This system was divided into five stages: surveillance, communication, system activation, direct management, and impact assessment. In October 2021, the system was implemented with satisfactory results after a bloom of the dinoflagellate Vulcanodinium rugosum. The implementation of this system contributed to mitigate the impacts of harmful algal blooms in different development sectors in the province of Cienfuegos.